Three Questions About the Social Life of Values. Issue 1 (2nd January 2021) - Walker, Harry
ABSTRACT: This afterword to the Qualifying Sociality through Values special issue reflects on the challenge, aptly considered by each contributor, to revamp and rejuvenate the sociality concept in light of the ethical turn. It poses three questions. Firstly, just how important are values for sociality? That is, to what extent is social action really conceived and executed through values? Secondly, how does sociality itself figure as a value, and how should we accommodate values that are not obviously prosocial such as separation and withdrawal? Thirdly, what is the relationship between competing values – when and how (if at all) do values genuinely conflict rather than complement or reinforce one other, and how do people then choose between them? These questions are crucial, I suggest, if we are to advance our understanding of how people embark on the shared project of crafting good and meaningful lives.